THE INSTITUTION OF RECONCILIATION IN TURKISH LAW (Journal of actual problems of jurisprudence, 2024)
According to the legal system currently applied in Turkey, the state initiates a public prosecution against individuals who commit crimes, and these individuals are punished after being tried in judicial courts. While this system has been in use for many years, the reconciliation procedure has recently been adopted in the Turkish legal system. Reflecting the restorative justice system inherent in our culture, the institution of reconciliation has emerged as an alternative path in our criminal justice system. The reconciliation procedure aims to restore the public order disrupted by the crime of the suspect or defendant through the parties' agreement before a court trial, facilitating the reintegration of the offender into society, while also ensuring quick compensation for the victim. The reconciliation institution, applied during the investigation phase, prevents the initiation of criminal proceedings against offenders, thereby alleviating the burden on the judicial prosecution phase. The reconciliation process serves to conclude potential criminal cases by enabling the parties to reach an agreement of their own free will, thus eliminating the threat of criminal investigation and prosecution. The reconciliation procedure concludes more quickly than criminal trials, thereby relieving the offender from prolonged judicial pressure, and if the victim consents to the proposed compensation, their losses are promptly recovered.Keywords: Reconciliation, Fair Trial, Restorative Justice, Criminal Law